Coping Strategies Among Mothers of Children with Eating Difficulty - Francisca A Tjakradidjaja (The Avicenna Medical Journal, 2020)
Background: The impact of eating difficulty in children can cause the intake of nutrients to be less, so the nutritional needs become unreachable. It is not easy for parents to face the fact that their children have eating difficulty. Coping becomes part of the adjustment. Coping is a special term used to indicate an individual's reaction when facing pressure or stress. Thus, the coping strategies of parents in dealing with children who have eating difficulty is requiredto deal with and control existing problems.Objective: The aim of this study was to explore the coping strategies of mothers who have children with eating difficulty.Methods: This research was a phenomenological qualitative research. Qualitative data collection techniques in this study was in-depth semi-structured interview techniques. Data analysis was performed by AtlasTi software. Content analysis was used to analyze raw data and identify overarching themes.Results: There four main themes and associated subthemes, were abstracted from the data, namely feeding problem manifestation (refusing to chew, throw out, prolonged mealtimes, inadequate food intake, food refusal, picky eating, closed mouth), stress full condition (angry/out of control, miserable, confused/puzzled, worried, impatient, frustrating), removed from the situation (positive thinking, ignored, acceptance, persevering, religious approaches),and action to modify situation (creative, seeking for help, looking for information, giving the nutrition supplement).Conclusion: This study may have implications for the implementation in overcoming child with eating difficulties. By understanding the mother's condition, then the treatment will be more focused and precise.